Activity‐based probes for the multicatalytic proteasome. (7th February 2017) - Hewings, David S.; Flygare, John A.; Wertz, Ingrid E.; Bogyo, Matthew
Abstract : Proteasomes are multisubunit protease complexes responsible for degrading most intracellular proteins. In addition to removing damaged proteins, they regulate many important cellular processes through the controlled degradation of transcription factors, cell cycle regulators, and enzymes. Eukaryotic proteasomes have three catalytic subunits, β1, β2, and β5, that each has different substrate specificities. Additionally, although we know that diverse cell types express proteasome variants with distinct activity and specificity profiles, the functions of these different pools of proteasomes are not fully understood. Covalent inhibitors of the protease activity of the proteasome have been developed as drugs for hematological malignancies and are currently under investigation for other diseases. Therefore, there is a need for tools that allow direct monitoring of proteasome activity in live cells and tissues. Activity‐based probes have proven valuable for biochemical and cell biological studies of the role of individual proteasome subunits, and for evaluating the efficacy and selectivity of proteasome inhibitors. These probes react covalently with the protease active sites, and contain a reporter tag to identify the probe‐labeled proteasome subunits. This review will describe the development of broad‐spectrum and subunit‐specific proteasome activity‐based probes, and discuss how these probes have contributed to our understanding of proteasome biology, and to the development of proteasome inhibitors. Abstract : The proteasome maintains proteostasis and regulates cellular processes through controlled protein degradation. Proteasome composition and activity can have profound effects on cellular functions, but are challenging to assess using conventional techniques. Activity‐based probes are powerful tools to understand the proteasome's role in normal and disease states.